Writings on the Spiritual Life - Evans, Christopher P. (Brepols, 2013)
The Canons following the Rule of St Augustine at St Victor in Paris were some of the most influential religious writers of the Middle Ages. They combined exegesis and spiritual teaching in a theology that was deeply rooted in tradition but also attuned to current developments in the schools of Paris. This selection of their writings on the spiritual life is divided into three sections. The first presents three works by Achard and Richard which treat the development of Christian life from the beginnings of conversion to the perfection of love and contemplation. Prayer, meditation and the gifts of the Holy Spirit are the subjects of the works by Hugh and Richard included in the second section. The final section presents poetical, exegetical and homiletic works honoring Mary by Hugh, Adam, Richard and Godfrey. This rich and representative sampling of Victorine works is a clear window into a world that still has much to offer modern readers interested in spirituality, medieval or modern. The editor of this volume is Christopher P. Evans (PhD, St Louis University; Department of Theology, University of St. Thomas, Houston, TX), the editor of Hildegard of Bingen’s <span class=